Synchronous reduction-fixation of reducible heavy metals from aqueous solutions: Application of novel mesoporous MFT/SBA-15 composite materials. (August 2021) - Yu, Ningya; Wu, Ke; Tao, Liang
Abstract: The usual treatment for Cr(VI)-contaminated wastewater primarily included reduction, adsorption, and the subsequent separation of the Cr-laden adsorbent. Among these factors, the adsorbent is the most critical factor in determining Cr removal efficiency. In this study, a novel melamine-formaldehyde-thiourea (MFT) chelating resin/mesoporous silica composite material (MFT/SBA-15) was synthesized via a co-condensation method and used for the reduction and fixation of Cr(VI)-contaminated water. Cr(VI) adsorption onto MFT/SBA-15 obeyed the pseudo-second-order model, and the chemical adsorption was the rate-limiting step in the adsorption process. Also it followed the Langmuir adsorption model, with single molecular layer adsorption characteristics. The organic components within MFT/SBA-15 were the core functional groups for Cr(VI) adsorption, and the formation of a coordination bond (CS→Cr) between the lone electron pairs of the S atom and Cr during the adsorption process led to the synchronous reduction-fixation processes of Cr(VI). These synchronous effects were further demonstrated for other reducible heavy metals, including As(V) and Cu(II), but negligibly observed in chemically stable elements, such as Zn(II), Ni(II), Pb(II), Cd(II), and As(III). The novel mesoporous MFT/SBA-15 materials combine the advantages of the chelating resin and mesoporous silica and have excellent potential for the wastewater treatment of reducible heavy metals through synchronous reduction-fixation. Graphical abstract: Image 1 Highlights: Novel mesoporous MFT/SBA-15 was synthesized via a co-condensation method. Organic components in material were the core functional group on Cr(VI) adsorption. S element in the organic components was the most significant component. MFT/SBA-15 treat reducible heavy metals through synchronous reduction-fixation.